Two new species of Kudinopasternakia Guţu, 1980 (Crustacea: Tanaidacea: Sphyrapodidae) with remarks on setology nomenclature - Dos Santos, Kátia Christol (Zootaxa, 2014)
Two new species of sphyrapodid tanaidaceans, Kudinopasternakia falconae n.sp. and Kudinopasternakia serejae n.sp., are described and illustrated from benthic samples taken at 680–790m depth in the Campos Basin, off the coast of south-eastern Brazil. The main characters used for the separation of the species are the number of maxillule palp distal setae, the number and length of spiniform setae on the ventral surface of the carpus and propodus of pereopod 1, the ornamentation of the ventral margin of the unguis of pereopods 4 to 6, and the pleonal epimera. Exopods were also observed on pereopods 4 and 5 of the manca of both new species. Some nomenclatural terms related to setae are discussed. A key to the genus Kudinopasternakia is presented.